Hypertension, Diabetes and Medication Adherence among the Older Supplemental Nutritional Assistance Program Population. (March 2022) - Heflin, Colleen; Hodges, Leslie; Ojinnaka, Chinedum O.; Arteaga, Irma
The burdens of chronic diseases such as hypertension and diabetes for older Americans are profound. Yet, data on the population-level prevalence of hypertension and diabetes among the older adult Supplemental Nutritional Assistance Program (SNAP) population and the associated level of medication adherence is lacking despite evidence of the "treat or eat" trade-off in the general population. We used linked administrative data from SNAP and Medicaid between 2006 and 2014 in the state of Missouri to document rates of hypertension or diabetes diagnoses and medication adherence. About 69% of the study sample were found to be diagnosed with a hypertension and 40% with diab etes. Approximately 1 in 4 of those living with hypertension and 1 and 3 of those living with diabetes were nonadherent to antihypertensive or antidiabetic medications each year, on average. Furthermore, medication non-adherence increases with age and is more common among non-White and urban residents.